ASIAN INDIAN MUSLIM NEGOTIATING FOR IDENTITY IN THE POST ‘SEPTEMBER ELEVENTH’ AS DEPICTED IN THE FILM MY NAME IS KHAN - Fajriani Fajriani (Rubikon : Journal of Transnational American Studies, 2014)
This article is an attempt to examine the problem of Muslim identity and how they negotiate their identity as Muslim whereas they have to face anti Muslim racism by Americans. The film has the theme of racism in the context of Muslim racial profiling. Therefore to accomplish the objectives, it applies Kant’s theory called as “races of mankind” that is, people are distinguishable according to their inherited physical attributes. This term illustrated the racialized of religion in the context of physical attributes related to labeling of Muslim racial profiling and stereotypes as terrorist. Since “September Eleventh”, Muslim is suspected as terrorist and has to be responsible for the tragedy. The interesting fact found in the analysisof the Asian Indian Muslim identity in the United States America post “September Eleventh” as depicted in the film is that, the Muslim Americans community was particularly impacted by the attacks and has had to face the growing Islamophobia including discrimination and prejudice, racial hatred, as well as violence. Rising Islamophobia and the negative reaction of American society to “September Eleventh” have led to changing definitions of the good multicultural society in the United States of America. Therefore, to decrease the impact of Islamophobia, Asian Indian Muslim Americans undergo the process of negotiation for their identity as Muslim through the way such as assertiveness in faith, showing the truth of Islam and participate in social activity. Accordingly, Americans Muslim can reduce the suspicionsof their identity until Americans do not assume them as threat even less as enemy but rather as human being that have right to be appreciated because of their humanity and not because of their identity as Muslim.